Digital activism and youth participation in Indonesia: A qualitative study of social media’s role in contemporary social movements - Nugroho, Bernardus Herdian (Privietlab, 2025)
Amidst Indonesia's evolving democratic landscape, digital activism has become a defining arena for youth-driven civic engagement. This qualitative research delves into how Indonesian youth are harnessing social media platforms to propel contemporary social movements. Drawing from in-depth case studies of two pivotal movements—#ReformasiDikorupsi and #TolakOmnibusLaw—and candid interviews with activists, this study uncovers the strategies, motivations, and profound challenges that they navigate. Our findings reveal that social media acts as a powerful catalyst for rapid mobilization and broad participation, effectively forging a collective identity and solidarity among youth activists. Online campaigns demonstrably amplify on-the-ground protests, contributing to tangible outcomes such as policy shifts. However, this empowerment is contested within a digital terrain fraught with significant obstacles. Activists must contend with the rampant spread of misinformation and harassment, an overreliance on virality to achieve impact, and the organized counter-mobilization of